Association between Dietary Pattern and Stress Level among Gastritis Patients at a Primary Health Care Center in West Halmahera Regency - Janeanti Afi Kayely; Heny Nurmayunita (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2026)
Gastritis is a common gastrointestinal disorder that is influenced by both behavioral and psychological factors, including dietary patterns and stress. This study aimed to examine the association between dietary patterns and stress levels among patients with gastritis at a primary healthcare center in West Halmahera Regency. A quantitative analytical study with a cross-sectional design was conducted in November 2025. A total of 60 gastritis patients were recruited using a total sampling technique. Data were collected using structured questionnaires to assess dietary patterns and stress levels. Statistical analysis was performed using SPSS version 26. Descriptive analysis was used to summarize respondents’ characteristics, while the Chi-square test or Fisher’s exact test was applied to analyze the association between variables. The results showed that most respondents had unhealthy dietary patterns and experienced high stress levels. Dietary pattern was significantly associated with stress level (p = 0.038), whereas demographic characteristics were not significantly related to stress level. Patients with unhealthy dietary patterns were more likely to experience high stress. In conclusion, dietary pattern is significantly associated with stress levels among gastritis patients. These findings highlight the importance of promoting healthy eating behaviors as part of stress management strategies in primary health care settings.